Mining the Ocean Genome: Global Bioprospecting Expeditions and Genomic Extractivism on the Oceanic Frontier - Amedeo Policante; Erica Borg (Archivio Antropologico Mediterraneo)
The article follows the ongoing transformation of genomic science into an industry – dedicated to the systematic extraction, abstraction and manipulation of genetic material – and considers the new types of oceanic exploration that genomic research both presupposes and fosters. We argue that emergent practices of ocean bioprospecting are sparking new ways of thinking, living and exploiting marine ecosystems as «genomic mines». We chart the recent history of genomic bioprospecting operations in the global ocean – focusing on the Sorcerer II expedition (2004-2006) and the Tara Oceans project (2009-2013) – and recount the rise of the «ocean genome» as an object of knowledge and a target of extractivist practices. Finally, we theorize the peculiar global mobility of bioprospecting vessels as constituting a practice of social construction of the ocean: a peculiar form of scientific navigation, which is already engendering new social uses of marine biodiversity, new strategies of capital accumulation, as well as innovative representations of ocean ecosystems.